Display behaviour and relationships of the Argentine Blue-billed Duck - Johnsgard, Paul A; Nordeen, Cristi (Wildfowl, 1981)
An analysis of the male postural displays of Argentine Blue-billed Ducks Oxyura vittata indicate that nearly all of these are derived from rather simple comfort movements which have been modified but little through ritualization. One ritualized posture (neck-jerking) appears to be unique to the species, and is also the most commonly performed display, whereas the most complex display (sousing) is very similar in form to the corresponding displays of the Australian Blue-billed Duck O. australis and the Maccoa Duck O. maccoa. A close evolutionary relationship among these three species is thus supported, and on the other hand there is no behavioural evidence suggesting a close phyletic relationship with the Peruvian Ruddy Duck O. jamaicensis ferruginea, a partially sympatric sibling species that is evidently part of the North American Ruddy Duck O. j. jamaicensis complex.